A New Class of Meromorphic Functions Involving the Polylogarithm Function. (11th August 2014) - Alhindi, Khadeejah Rasheed; Darus, Maslina
Abstract : We introduce a new operatorD c f ( z ) associated with polylogarithm function. By making use of the new operator, we define a certain new class of meromorphic functions and discussed some important properties of it.